9 Penerapan Model Pembelajaran Sentra Bermain Peran Dalam Upaya Meningkatkan Sosial Emosional Anak Usia Dini 4-5 Tahun - Husnah, Asmaul (AT-THUFULY : Jurnal Pendidikan Islam Anak Usia Dini, 2024)
This study aims to address several key issues, namely how the implementation of the Role-Playing Learning Center Model can improve the social skills of early childhood children aged 4-5 years at KB Al Hayat Jatikalang Krian. What are the challenges faced in implementing the Role-Playing Learning Center Model to enhance the social skills of early childhood children aged 4-5 years at KB Al Hayat Jatikalang. And what are the solutions to overcome the challenges in implementing the Role-Playing Learning Center Model to improve the social skills of early childhood children aged 4-5 years at KB Al Hayat Jatikalang. The research uses a qualitative model with a case study approach. The implementation of the role-playing learning center model at KB Al Hayat Jatikalang Krian involves preparing predetermined tools such as themes, lesson plans (RPPH), density, intensity, learning SOPs, and child development assessments. In all learning processes, encountering obstacles is common, but these obstacles do not always carry a negative connotation; the important thing is that evaluation and improvement occur in response to these challenges. Every challenge certainly has accompanying solutions, as is the case with the obstacles encountered in the learning centers at KB Al Hayat. The following are solutions that can be used to address these challenges. Facing inadequate media challenges, considering the already good school conditions, it would be beneficial for the school to add facilities for students to support the progress and smoothness of the teaching and learning process to ensure the accountability of the children's outcomes.